APPLICATION OF NANOSTRUCTURES IN PHOTOVOLTAIC ENERGY SOURCES - Eshboltayev Iqbol Mamirjonovich; G‘ofurov Saidkamol Zokirjon ogli; Eshboltayev Ikromjon Iqbol ogli (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract This paper discusses the application of nanostructures and nanomaterials in photovoltaic (PV) energy sources, their main types, operating mechanisms, and their role in improving the efficiency of solar cells. New-generation solar cells developed based on nanotechnologies enable increased energy conversion efficiency, reduced material consumption, and the creation of flexible and low-cost energy sources.